Contextualizing a framework for improving postnatal care in Ethiopia - Bala, Elias Teferi; Roets, Lizeth (Frontiers in Public Health, 2022)
Background: Postnatal care is among the major recommended interventions to reduce maternal deaths. To improve the low postnatal care utilisation in Ethiopia, framework developed for this purpose in Kenya, was contextualised and adapted for implementation in the Ehiopian context . Objectives: The objectives of this article is to share the process followed to contextualise Chelagat’s framework for improving postnatal care, for implementation in Ethiopia as well as the finalised contextualised framework. Methods: A quantitative descriptive research design was adopted. A self-administered questionnaire was used to gather data during November 2018 from 422 postnatal care providers and coordinators, using stratified random sampling. The AGREE II was utelised to assess adoptability and applicability and an open ended question allowed to assess challenges and opportunities for utelising the framework. Data were analysed using SPSS computer software version 23. Results: The findings revealed that the framework from Chelagat was adoptable to use for the improvement of postnatal care in the Ethiopian context. The result from the analysis of the data using AGREE II indicated an average domain score of 92%, for contextualisation possibility. Conclusion: The framework originally developed by Chelagat was contextualised and refined to be implemented in Ethiopia to improve postnatal care.